A Transgenic Mouse Model of Pacak–Zhuang Syndrome with An Epas1 Gain-of-Function Mutation - Wang, Herui (Cancers (Basel), 2019)
We previously identified a novel syndrome in patients characterized by paraganglioma, somatostatinoma, and polycythemia. In these patients, polycythemia occurs long before any tumor develops, and tumor removal only partially corrects polycythemia, with recurrence occurring shortly after surgery. Genetic mosaicism of gain-of-function mutations of the EPAS1 gene (encoding HIF2α) located in the oxygen degradation domain (ODD), typically p.530–532, was shown as the etiology of this syndrome. The aim of the present investigation was to demonstrate that these mutations are necessary and sufficient for the development of the symptoms. We developed transgenic mice with a gain-of-function Epas1(A529V) mutation (corresponding to human EPAS1(A530V)), which demonstrated elevated levels of erythropoietin and polycythemia, a decreased urinary metanephrine-to-normetanephrine ratio, and increased expression of somatostatin in the ampullary region of duodenum. Further, inhibition of HIF2α with its specific inhibitor PT2385 significantly reduced erythropoietin levels in the mutant mice. However, polycythemia persisted after PT2385 treatment, suggesting an alternative erythropoietin-independent mechanism of polycythemia. These findings demonstrate the vital roles of EPAS1 mutations in the syndrome development and the great potential of the Epas1(A529V) animal model for further pathogenesis and therapeutics studies.